The path to perfect stays: understanding brand image and technological convenience impact on customer satisfaction in Penang’s luxury hotels / Mohd Zool Fadli Ibrahim ... [et al.] - Ibrahim, Mohd Zool Fadli; Mohamad Saber, Joesri; Bahari, Khairil Anuar; Abu Bakar, Muhammad Aiman Alif; Abu Mansor, Nur Aina Afiqah (Universiti Teknologi MARA, Perlis, 2025)
In the hospitality sector, the success of hotels is intricately tied to customer satisfaction, which serves as a critical performance metric and influences competitiveness in the market. 5-star hotels on Penang Island face increasing challenges to sustain guest satisfaction amidst growing competition. Despite the growth of the luxury accommodation sector, there is still much to learn about what truly drives customer satisfaction and loyalty in specific local contexts. Previous research points to factors like brand image and technological convenience as a key influence on customers when choosing luxury hotels. However, many studies overlook how these factors play out in localized markets. This study focuses on Penang Island’s 5-star hotels, exploring how brand image and technological convenience shape customer satisfaction. Drawing on feedback from 390 guests who stayed in selected luxury hotels in the region, the results reveal a clear link: brand image and technological convenience significantly impact customer satisfaction. These insights highlight the need for hotels to adapt their strategies to meet the changing expectations of their guests, ultimately fostering stronger customer loyalty. The insights gained contribute to developing comprehensive strategies to sustain excellence in the competitive landscape of Penang’s luxury hotel industry